The fair and good (Iter, 2022)
Kalokagathoi and kalokagathía have been interpreted either as ethical concepts. or associal notions. The present note examines their employment in some texts o f Greek ClassicalAge.
Keywords: kalokagathoi - kalokagathía - aristocracy - fairness - society